2019
DOI: 10.1186/s12957-019-1640-6
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction after unilateral oncoplastic volume displacement surgery for breast cancer, evaluated with the BREAST-Q™

Abstract: Background Oncoplastic breast-conserving surgery allows larger resections in unfavorable locations, with an improved chance of preserving esthetics. Indications and timing for potential contralateral surgery to obtain symmetry are not clear. The aim of this study was to evaluate patient satisfaction after unilateral oncoplastic volume displacement surgery, to investigate potential risk factors for lower patient satisfaction and to assess patient wish for contralateral surgery. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 34 publications
2
14
1
Order By: Relevance
“…All differences were statistically significant, showing that distinct improvement in the physical level occurs during the first year after surgery. These results do not match our expectations, and means of “physical well-being” scores reported by other studies after BCT have been noticeably higher (e.g., 67 during a follow-up period of 12 months, 32 78 during a median follow-up period of 28 months, 47 80 during 5 to 7 years from surgery to survey, 26 and 81 during a median follow-up period of 5.5 years. 28 These studies all had different time frames for the follow-up evaluation, which surely in part explains the variation in the results.…”
Section: Discussioncontrasting
confidence: 99%
“…All differences were statistically significant, showing that distinct improvement in the physical level occurs during the first year after surgery. These results do not match our expectations, and means of “physical well-being” scores reported by other studies after BCT have been noticeably higher (e.g., 67 during a follow-up period of 12 months, 32 78 during a median follow-up period of 28 months, 47 80 during 5 to 7 years from surgery to survey, 26 and 81 during a median follow-up period of 5.5 years. 28 These studies all had different time frames for the follow-up evaluation, which surely in part explains the variation in the results.…”
Section: Discussioncontrasting
confidence: 99%
“…One study of 120 patients undergoing oncoplastic breast-conserving surgery found a median score of 74 of 100 on the BREAST-Q domain for satisfaction with breasts, with 91% of patients reporting that the operation entirely or almost entirely met their expectations regarding the cosmetic outcome. 28 In a study of 155 women treated with oncoplastic breast conserving surgery, including mammoplasty or LD flap, overall satisfaction with breast surgical outcomes was 82 of 100. 29 It should be noted that of these two techniques, those patients treated with an LD flap reported more back and shoulder symptoms and upper back pain.…”
Section: Assessment Of Patient-reported Outcomes With Oncoplastymentioning
confidence: 99%
“…Duration of drain placement varied between 3 and 14 days with removal if the fluid output was less than 25 cc in a day. Duration of surgery from the time of first incision (excluding any axillary surgery) was between 45 and 323 min [median (IQR): 105 [ 25 ]]. 9 patients had their LPF surgery as a daycare procedure and the duration of the entire hospital stay ranged from 5 to 52 h [median (IQR): 24 (41)].…”
Section: Resultsmentioning
confidence: 99%